Paper bacterial battery based on polymer as degradable sources of energy - M Haleem, Azhar; H Abass, Ruaa; M Haleem, Israa (International Journal of Advanced Chemistry, 2021)
Paper bacterial battery (PBB) is a sustainable source of bioenergy derivate from bacterial activities, paper bacterial battery or microbial fuel cell has unique features like biodegradable, cost- affordable, energy- effectiveness, and environmental sounds beside of complete control by produced energy by increasing the number of folds and can made it in shapes and sizes appropriate for all use and type of devices, which is characterized by high flexibility and wide uses. The current study described in detail the fabrication steps of a simply biodegradable paper battery that mainly composed of a substrate of cellulose, Poly (amic) acid (PAA) and polyvinyl alcohol (PVA) as reducing and stabilizing agent, immobilization matrix, for bacterial cells stability, this degradable network provides oxygen-blocking and proton exchange membrane (PEM). The fabricated bacterial battery gave power of 3.5 ÂµW/cm2 and a current quantity of 127 ÂµA/cm2, this generated power can be enhancement by more folding or compacting of the fabricated paper-polymer unit.Â Â